Iplementasi Penilaian Proyek Pada Pembelajaran Matematika Berbasis Lesson Study Di MTs Muhammadiyah Waru(Pada Siswa Kelas VII Semester Ganjil Tahun 2016/2017) - Ahmad Alfian, Ilham; Dr. Sumardi, M.Si (2017)
The purpose of this research was (1)to know math teacher at MTs Muhammadiyah Waru for understanding the project, (2) describing the implementation assessment of the project on learning math based lesson study, (3) describes constraints in implementing the project on learning math lesson study. Research had done in MTs Muhammadiyah Waru in the category VII A and B, where is teacher as an action to students and researchers as an observer. Blast me, indentify problems, make the concept of teaching and planned actions. The research is a research sort of descriptive set of qualitative. The collection of data used among others, observation, interviews and documentation. The analysis of data used the reduction of data, the presentation of data withdrawal of a conclusion. This research result indicates that, the theacher has to understand about the project but had never done, while the assessment. The project by applying the plan, do and see improve the performance or thacher, motivating study math students in grade VII and help students in order to determine, the attitude and skills beter. the obstacle faced by the absence of LCD, the time that was cut 10 to 15 minutes of the first hour of learning and have not a place to the reflection.